Comparative Study on Cold Compaction Behavior of TiH2 Powder and HDH-Ti Powder - Shucheng Dong; Baicheng Wang; Yuchao Song; Guangyu Ma; Huiyan Xu; Dmytro Savvakin; Orest Ivasishin (Advances in Materials Science and Engineering)
The compaction mechanism of titanium hydride powder is an important issue because it has a direct impact on density and strength of green compacts and ultimately on the physical and mechanical properties of a final sintered products. In this paper, the characteristics and compaction behavior of titanium hydride and hydrogenation-dehydrogenation titanium powders are comparatively studied and analyzed for better understanding of compaction mechanism of brittle low-strength titanium hydride. The results indicate that the particles of titanium hydride powder are easily crushed under compaction loading at relatively low pressure well below compression strength of bulk titanium hydride, the degree of particle crushed increases with the increase of pressure. The compaction behavior of titanium hydride powder mainly includes the rearrangement and crushing of particles in the early compaction stage, minor plastic deformation, if any, and further rearrangement of particle fragments with filling the pores in the later stage. Such compaction behavior provides relative density of green hydride compacts higher than that for titanium powder of the same size. The relatively coarse titanium hydride powder with wide particle size distribution is easier to fill the pores providing highest green density.